Regulated programmed cell death in acute lung injury: from pathogenesis to therapy - Shi-wen Liu; Shi-wen Liu; Yi-jian Chen; Yi-jian Chen; Yi Liu; Wen Zhou; Wen Zhou; Xuan Liu; Xuan Liu (Frontiers in Immunology)
Acute lung injury (ALI) is a common, life-threatening lung disease with a high mortality rate, primarily associated with acute and severe inflammation of the lungs. There are many factors that lead to ALI, and abnormally advanced regulated programmed cell death (RCD) is considered to be an important process in the pathological process of ALI. Various forms of RCD have been discovered in recent years, including apoptosis, necroptosis, autophagy, ferroptosis and pyroptosis. Unlike necrosis, RCD is an active cell death mediated by a series of gene expression events that is essential for eliminating unnecessary and damaged cells as well as defense mechanisms. Previous studies have shown that RCD has a strong relationship with ALI. Therefore, it is important to describe the role of RCD not only to enhance our understanding of the pathophysiological processes of ALI, but also to improve the functional recovery after ALI. This review reviews the roles and mechanisms of various RCD (apoptosis, pyroptosis, necroptosis, ferroptosis and autophagy) in ALI, and discusses the associations among various types of RCD. The aim is to explore the molecular mechanism behind SALI and find new targets for the treatment of ALI. This review will help us understand the various functions and mechanisms of RCD in the pathological process of ALI, and help us to treat various ALI of unknown etiology.